Perceived Impact of Spasticity Is Associated with Spatial and Temporal Parameters of Gait in Multiple Sclerosis. (17th January 2012) - Balantrapu, Swathi; Sandroff, Brian M.; Sosnoff, Jacob J.; Motl, Robert W.
Abstract : Background . Spasticity is prevalent and disabling in persons with multiple sclerosis (MS), and the development of the Multiple Sclerosis Spasticity Scale-88 (MSSS-88) provides an opportunity for examining the perceived impact of spasticity and its association with gait in this population. Purpose . This study examined the association between the perceived impact of spasticity and spatio-temporal parameters of gait in persons with MS. Methods . The sample included 44 adults with MS who completed the MSSS-88 and 4 walking trials on a 26-foot GAITRite TM electronic walkway for measurement of spatio-temporal components of gait including velocity, cadence, base of support, step time, single support, double support, and swing phase. Results . The overall MSSS-88 score was significantly associated with velocity (r = − 0.371 ), cadence (r = − 0.306 ), base of support (r = 0.357 ), step time (r = 0.305 ), single leg support (r = − 0.388 ), double leg support (r = 0.379 ), and swing phase (r = − 0.386 ). Conclusions . The perceived impact of spasticity coincides with alterations of the spatio-temporal parameters of gait in MS. This indicates that subsequent interventions might target a decrease in spasticity or its perceived impact as an approach for improving mobility in MS.